2013
DOI: 10.1021/jo402055a
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted Acid Catalyzed and NIS-Promoted Cyclization of Diynones: Selective Synthesis of 4-Pyrone, 4-Pyridone, and 3-Pyrrolone Derivatives

Abstract: Brønsted acid catalyzed tandem cyclization was found to be highly effective for the preparation of a series of polysubstituted 4-pyrones from diynones (yield up to 99%). 4-Pyridone and 3-pyrrolone derivatives were also selectively synthesized by employing NIS and/or Brønsted acid. NIS as an electrophilic reagent could promote these reactions efficiently and rapidly under very mild reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 84 publications
3
31
0
Order By: Relevance
“…Moreover, an O 18 -labeled experiment further showed that H2O reacted with diynones to form 4-pyrones. On the basis of the above results and existing literature [78], a plausible mechanistic description of the nucleophilic addition and cyclization reaction is shown in Scheme 2. First, the carbonyl of the diynone substrate was activated by TfOH, followed by nucleophilic addition of H2O to the carbon−carbon triple bond of diynone and keto−enol tautomerization [79,80] The treatment of 1,5-diphenylpenta-1,4-diyn-3-one 1a in H2O at 100 °C for 36 h in the presence of TfOH afforded the corresponding cyclization product 2a in 83% yield.…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…Moreover, an O 18 -labeled experiment further showed that H2O reacted with diynones to form 4-pyrones. On the basis of the above results and existing literature [78], a plausible mechanistic description of the nucleophilic addition and cyclization reaction is shown in Scheme 2. First, the carbonyl of the diynone substrate was activated by TfOH, followed by nucleophilic addition of H2O to the carbon−carbon triple bond of diynone and keto−enol tautomerization [79,80] The treatment of 1,5-diphenylpenta-1,4-diyn-3-one 1a in H2O at 100 °C for 36 h in the presence of TfOH afforded the corresponding cyclization product 2a in 83% yield.…”
Section: Resultsmentioning
confidence: 70%
“…The general procedure was used with 1,5-bis(4-methoxyphenyl)penta-1,4-diyn-3-one (145.05 mg, 0.5 mmol, 1 equiv.) and water (1 mL [78]. The general procedure was used with 1,5-bis(4-ethylphenyl)penta-1,4-diyn-3-one (143.07 mg, 0.5 mmol, 1 equiv.)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The only significant modifications are related to the substrate generation [15] or the nature of the leaving group involved in the cyclization step [1618]. More recently, an elegant acid-catalyzed cyclization of diynones has also been described [19]. Despite undeniable synthetic efficiency, these approaches require harsh reaction conditions or the time-consuming preparation of elaborate substrates.…”
Section: Introductionmentioning
confidence: 99%